Evaluación de diversos tamaños de sitio de muestreo en inventarios forestales - Aguirre Calderón, Oscar A.; Jiménez Pérez, Javier; Treviño Garza, Eduardo J.; Meraz Alemán, Blas (Instituto de Ecología, A.C., 2016)
A n evaluation of different sampling plot sizes was carried out on a Pinus cooperi Blanco stand in the region of El Salto, Durango, Mexico to determine optimal plot size for forest inventory.  A complete census was carried out in a 4.4 ha area and 36 plots of 0.1 ha were established. Plot sizes of 0.01 to 0.1 ha, with intervals of 0.01 ha were tested using a fixed dimensions plot simulator. Based on the statistical parameters of the basal area, optimal plot size was 0.06 ha.